Does Pepsin Saliva Concentration (Peptest™) Predict the Therapeutic Response of Laryngopharyngeal Reflux Patients?. (September 2021) - Lechien, Jerome R.; Bobin, Francois; Dequanter, Didier; Rodriguez, Alexandra; Le Bon, Serge; Horoi, Mihaela; Thill, Marie-Paule; Salem, Charelle; Muls, Vinciane; Saussez, Sven
Objective: To study the profile and the therapeutic response of patients with laryngopharyngeal reflux (LPR) at the hypopharyngeal-esophageal multichannel intraluminal impedance-pH monitoring (HEMII-pH) according to the initial pepsin saliva concentration. Methods: From January 2018 to January 2020, patients with positive LPR diagnosis at the HEMII-pH were consecutively recruited from 3 European Hospitals. Saliva pepsin concentration (Peptest™) was measured during the HEMII-pH testing period and patients were classified into 2 groups: negative versus positive Peptest. The clinical outcomes, that is, gastrointestinal and HEMII-pH findings, reflux symptom score-12 (RSS-12), and 3-month therapeutic response, were compared between groups. Results: A total of 124 patients completed the study. Among them, 30 patients had negative Peptest. Pharyngeal reflux events occurred outside 1-hour post-meal time in 74.0%, after the meals in 20.5% and nighttime in 5.5%. The pepsin saliva level was not significantly associated with the reflux events preceding the sample collection. Patients with positive Peptest had better improvement of RSS-12 digestive and respiratory subscores and oral, pharyngeal, and laryngeal findings compared with patients with negative Peptest. Conclusion: Patients with high saliva pepsin concentration had no stronger gastrointestinal, HEMII-pH, or clinical outcomes compared with those with low or undetectable saliva pepsin concentration.